Investigation of acoustic transmission beneath a railway vehicle by using statistical energy analysis and an equivalent source model. (March 2021) - Li, Hui; Thompson, David; Squicciarini, Giacomo; Liu, Xiaowan; Rissmann, Martin; Denia, Francisco D.; Giner-Navarro, Juan
Highlights: Modelling approach for the noise beneath a train floor applied to rolling noise. Direct and reverberant sound is calculated and relative contributions quantified. The approach is verified by comparison with laboratory and field measurements. Improved understanding of the acoustic behaviour beneath the train floor. Abstract: An approach is presented for modelling the noise propagation beneath the train floor and this is applied to rolling noise sources. It is assumed that the sound incident on the train floor is made up of a direct and a reverberant component. A combination of two numerical modelling approaches is considered to deal with these: an equivalent source model, to represent the direct component, and statistical energy analysis (SEA) for the reverberant part. In the equivalent source model, the wheel is replaced by monopole and dipole sources, which represent its radial and axial radiation. The rail vertical vibration and the sleepers are replaced by arrays of monopole sources while the rail lateral vibration is replaced by an array of lateral dipoles. The sound power of the rolling noise is obtained by using the TWINS model. In the SEA model, the region beneath the train floor is divided into several volumes and the power input to these subsystems is assumed to be due to the first reflections from the train floor and the ground. The reverberant and direct sound have very similar contributions to the total sound power incident on the train floor although this depends on how the equipment is arranged beneath the train. The modelling approach is verified by comparing the predicted sound pressure levels with laboratory measurements and with field tests.